2017
DOI: 10.15252/embr.201643184
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte SIRT1 controls systemic insulin sensitivity by modulating macrophages in adipose tissue

Abstract: Adipose tissue inflammation, characterized by augmented infiltration and altered polarization of macrophages, contributes to insulin resistance and its associated metabolic diseases. The NAD-dependent deacetylase SIRT1 serves as a guardian against metabolic disorders in multiple tissues. To dissect the roles of SIRT1 in adipose tissues, metabolic phenotypes of mice with selective ablation of SIRT1 in adipocytes and myeloid cells were monitored. Compared to myeloid-specific SIRT1 depletion, mice with adipocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 56 publications
4
62
1
1
Order By: Relevance
“…By concordant gene expression patterns, we have been able to segregate the polarization state of adipose macrophages close to an M1 status with milk cream and to an M2 status with olive oil either without or with EPA and DHA supplementation, reconcilable with lower transcriptional activities of pro‐inflammatory genes and higher transcriptional activities of anti‐inflammatory genes (IL‐10 and IL‐4) in WAT of mice fed with olive‐oil‐based HFDs. IL‐4 expression is induced by SIRT1 in adipocytes and via PPARγ supports the alternative activation M2 in adipose macrophages . Our study further points to a low adipose inflammation and thereby the safeguard of WAT homeostasis when, in combination with niacin, the predominant dietary fat during HFD‐induced obesity and metabolic syndrome is olive oil.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…By concordant gene expression patterns, we have been able to segregate the polarization state of adipose macrophages close to an M1 status with milk cream and to an M2 status with olive oil either without or with EPA and DHA supplementation, reconcilable with lower transcriptional activities of pro‐inflammatory genes and higher transcriptional activities of anti‐inflammatory genes (IL‐10 and IL‐4) in WAT of mice fed with olive‐oil‐based HFDs. IL‐4 expression is induced by SIRT1 in adipocytes and via PPARγ supports the alternative activation M2 in adipose macrophages . Our study further points to a low adipose inflammation and thereby the safeguard of WAT homeostasis when, in combination with niacin, the predominant dietary fat during HFD‐induced obesity and metabolic syndrome is olive oil.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to what is seen with NAMPT, the expression of adipose sirtuins (SIRTs) that use NAD + as their substrate is lower in obese subjects and decreases in mice on HFD . The reputation of SIRTs in integrating metabolism and immunity is emphasized by the increased number of adipose‐resident and M1 macrophages found in mice with adipocyte‐selective SIRT1 deletion . Furthermore, the fuel of NAD + for SIRTs is severely compromised by other NAD + consumers such as the cluster of differentiation 38 (CD38) whose deletion phenocopies the condition of SIRT1 activation in WAT .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…10,22 This finding was supported by Aimin et al, who have found that disruption of glucose homeostasis by specific inactivation of SIRT1, a key regulator for glucose metabolism in adipocytes, exacerbates macrophage infiltration and the pro-inflammatory M1 polarization of ATMs, which, at least in part, leads to the aggravation of systemic glucose intolerance and insulin resistance at the early stage in obese mice, suggesting a necessary relationship between the glucose metabolism in AT and ATM polarization. 23 In addition, treating ATMs with glucose induced a "metabolically activated" pro-inflammatory phenotype in obese humans or mice that is positively correlated with adiposity. 10 More recently, emerging studies indicated that the abnormal glucose metabolism in macrophages can dramatically accelerate the development of CVDs.…”
Section: Glucose Metabolismmentioning
confidence: 99%